Pengaruh Kompres Jahe Terhadap Penurunan Nyeri Artritis Reumatoid Pada Lansia - kusyani, Asri; Aziz, Aditya Nuraminudin; Andriyani, Lisa (LPPM STIKes Bahrul Ulum Jombang, 2018)
Rheumatoid arthritis is an autoimmune disease of stiffness, swelling, pain and redness in the joints and surrounding tissues. The purpose of this study was to determine the effect of ginger compress on the decrease of rheumatoid arthritis pain in elderly in werdha sub-district mojokerto mojokerto district, this research is pre experiment with design of One-Group Pre-test Post-test Design. The population of 20 people with a sample of 20 respondents sampling technique total sampling with the implementation of compress ginger in the morning and afternoon, for 20 minutes for 1 week. This research was conducted to determine the influence of ginger compress pre- and post treatment. Then in the analysis to differentiate the decline. Data analysis was done by different test statistic that paired t test. The results obtained p-value = 0,000 (<0.05) where there are differences in scale before and last pain given a ginger compress. There is influence of ginger compress on the reduction of rheumatoid arthritis pain. One way to relieve arthritis pain is by way of compress ginger.